2021
DOI: 10.1002/anbr.202100021
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Prussian Blue Nanoparticles‐Based Nanoimmunotherapy Elicits Robust and Persistent Immunological Memory in a TH‐MYCN Neuroblastoma Model

Abstract: A combination therapy using Prussian blue nanoparticles (PBNP) as photothermal therapy (PTT) agents coated with CpG oligodeoxynucleotides, an immunologic adjuvant, as a nanoimmunotherapy (CpG‐PBNP‐PTT) for neuroblastoma (NB) is described. NB driven by MYCN amplification confers high risk and correlates with a dismal prognosis, accounting for the majority of NB‐related mortality. The efficacy of the CpG‐PBNP‐PTT nanoimmunotherapy in a clinically relevant, TH‐MYCN murine NB model (9464D) overexpressing MYCN is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 75 publications
(115 reference statements)
1
20
0
Order By: Relevance
“…PTT using aFn14-PBNP elicited thermally induced cell death in both GBM tumor lines as evidenced by a decrease in cellular viability in a laser power-dependent manner ( Figure 3 A). For U87 cells, the cellular viability decreased from 97.85% for aFn14-PBNP (without the laser) to 42.95% at 0.75 W, with the lowest viability of 18.45% observed at the highest laser power of 2 W. Similarly, for U251 cells, the cellular viability decreased from 95.00% for aFn14-PBNP (without the laser) to 55.25% at 0.75 W, with the lowest viability of 11.19% observed at the highest laser power of 2 W. For both tumor lines, the IC50 was attained at thermal doses of 4.72 for U87 and 4.86 for U251, respectively corresponding to a laser power of 0.75 W. These findings with aFn14-PBNP-based PTT in GBM tumor cells are consistent with our observations when using PBNPs for PTT in diverse tumor cell lines such as neuroblastoma, melanoma, and breast cancer [ 9 , 10 , 42 , 43 ]. We did not conduct studies assessing the effects of PBNPs alone (without the laser) as we have extensively observed that the PBNPs have a negligible effect on tumor cellular viability at the concentrations used for this study [ 9 , 10 , 42 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…PTT using aFn14-PBNP elicited thermally induced cell death in both GBM tumor lines as evidenced by a decrease in cellular viability in a laser power-dependent manner ( Figure 3 A). For U87 cells, the cellular viability decreased from 97.85% for aFn14-PBNP (without the laser) to 42.95% at 0.75 W, with the lowest viability of 18.45% observed at the highest laser power of 2 W. Similarly, for U251 cells, the cellular viability decreased from 95.00% for aFn14-PBNP (without the laser) to 55.25% at 0.75 W, with the lowest viability of 11.19% observed at the highest laser power of 2 W. For both tumor lines, the IC50 was attained at thermal doses of 4.72 for U87 and 4.86 for U251, respectively corresponding to a laser power of 0.75 W. These findings with aFn14-PBNP-based PTT in GBM tumor cells are consistent with our observations when using PBNPs for PTT in diverse tumor cell lines such as neuroblastoma, melanoma, and breast cancer [ 9 , 10 , 42 , 43 ]. We did not conduct studies assessing the effects of PBNPs alone (without the laser) as we have extensively observed that the PBNPs have a negligible effect on tumor cellular viability at the concentrations used for this study [ 9 , 10 , 42 ].…”
Section: Resultssupporting
confidence: 87%
“…ICD can convert an immunologically “cold” tumor to a “hot” one, where released antigens can activate an immune response against the tumor. Our group and others have previously shown that PBNP-mediated PTT can induce ICD in pediatric neuroblastoma [ 9 , 10 , 41 , 42 ], melanoma [ 43 ], and triple-negative breast adenocarcinoma preclinical models, to name a few, and is being investigated in this study as a novel treatment option for GBM. ICD is not always induced by nanoparticle-mediated PTT, but the consistency with which our lab has observed PBNP-PTT-induced ICD makes PBNPs an attractive material.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, PB NPs can simulate a variety of antioxidant enzyme activities, which has attracted great attention in the treatment of inflammatory diseases in recent years. [71][72][73][74][75] As shown in Figure 4, Zheng et al developed a PB NPs (PBzyme) that can act as a nano-enzyme to remove a variety of ROS and pro-inflammatory factors including •OH, •OOH, and H 2 O 2 . It reduces necrosis, nucleic acid damage, and peroxidation by downregulating TLR-related NF-κB signaling pathway Similarly, the rare earth element nanoparticles also have ROS scavenging properties.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…Juliana et al demonstrated that combination of PTT with nanomaterials containing immune adjuvant and CTLA-4 monoclonal antibody improved T-cell levels and inhibited tumor growth in NB mice, while exerting a memory effect to suppress tumor recurrence, with superior therapeutic efficacy than CTLA-4 monoclonal antibody or PTT therapy alone ( Cano-Mejia et al, 2017 ). They showed in their mouse model of TH-MYCN gene-driven malignant NB that PTT therapy with PBNP coated with the immune adjuvant CpG oligonucleotide (CpG-PBNP-PTT) was effective in regressing mouse tumors, improving survival time and activating t cell-mediated systemic immune responses ( Figure 6A ) ( Shukla et al, 2021 ). Similarly, combining CpG-PBNP with anti-CTLA-4 immunotherapy can not only cause ablative cell death, but also alter the surface levels of co-stimulatory, antigen-presenting, and co-inhibitory molecules on NB cells ( Cano-Mejia et al, 2020 ).…”
Section: Nanotechnology Enhances Therapeutic Treatment For Neuroblastomamentioning
confidence: 99%
“…(A) Schematic of the mechanism of action of the CpG-PBNP-PTT-based nanoimmunotherapy in the TH-MYCN model of NB. Reproduced with permission from ( Shukla et al, 2021 ). Copyright 2021, Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Nanotechnology Enhances Therapeutic Treatment For Neuroblastomamentioning
confidence: 99%